Rancang Bangun Purwarupa Alat Pengupas Buah Salak Berbasis Mikrokontroler - Taufik Taufik; Joko Saputro (Sistem Komputer & Teknologi Intelegensi Artifisial (SIKOMTIA), 2022)
Snakefruit is a fruit that is widely known by the people of Indonesia, many varieties of salak plants have superior properties both in terms of taste and appearance of the fruit. The process of stripping the salak fruit itself still uses the manual method (by hand) or by using a kitchen knife. This peeling process is one of the obstacles in the production of salak fruit as a basic product because it takes a lot of time to peel a single salak fruit and requires extra precision so that the hands are not injured due to the rough texture of the salak skin. So the purpose of this research is to make a prototype of a snake fruit peeler using an Arduino microcontroller as a data processor using several other supporting sensors such as the TCS3200 color sensor as a detector for the color of the skin of the snake fruit and a stepper motor to drive the wheels on the machine. to facilitate the purpose of trading business as well as how the work of the tool in an efficient method and productivity that is more competent and useful.